Locke and Rousseau: From Natural Freedom to The Social Contract - Yelubayev, Bainur; Olay, Csaba (Conatus - Journal of Philosophy, 2025)
John Locke and Jean-Jacques Rousseau are two eminent proponents of the contractual tradition, which asserts that political power is artificial, and its legitimacy stems from individual consent. The fundamental and common feature of all classical social contract theories is that the agreement concluded by all its participants is considered the basis of a true political body. Accordingly, only a political association based on the concept of a contract can create a form of government that binds naturally free people. The primary purpose of this work is to analyse and compare the contractual views of Locke and Rousseau. Thus, in the first chapter, we will explore Locke’s main contractual ideas, developed in his book Two Treatises of Government, emphasising the concepts of the law of nature and private property. In chapter two, we will examine Rousseau’s political ideas, particularly on human nature and the general will. Then, in the end, we will attempt to outline the differences and similarities between their views about the social contract.